FAKTOR-FAKTOR BROADEN BUILD YANG MEMPENGARUHI KINERJA KELEMBAGAAN PADA LEMBAGA SEKURITAS DI MALANG - Rahadjeng, Erna Retna (Journal of Innovation in Business and Economics, 2014)
This study aims to identify the performing of an agency applying nuturing institutional capital markets through built Broaden approach to improve the performance of securities institution. This phenomenological study was conducted on securities agency in Malang. The data has been collected by using participant observation, in-depth interviews, and questionnaires. The data was anlyzed by using content analysis. Based on the result, the researcher concluded that the variables (x1) Emotional Resiliency; (x2) Cognitive Resiliency; (x3) social resiliency; and Financial Resiliency (x4) have jointly significant influence on the performance of securities agency. Similarly, each variable partially has an influence on financial performance. The dominant variable influencing the performance of securities agency is cognitive resiliency variable that has the highest value of regression coefficient. Therefore, the hypothesis stated about there is an influence of emotional resiliency; cognitive resiliency; social resiliency; and financial resiliency variables towards the performance of the securities agency in Malang is accepted.